Peran Guru Bimbingan dan Konseling Dalam Menguatkan Moral Karakter Siswa dengan Metode Narasi - Zahrila Ismail (PENCERAHAN, 2023)
In the modern digital environment, technology is used in almost every area of schooling. Teaching and learning are becoming increasingly complex and personal, especially with the use of technology, and this has an impact on students' moral character. Guidance and counseling in schools is a basic need to assist pupils in developing self-concept, facilitating self-adjustment to their challenges, and developing hobbies, as well as developing social and personal skills. It seeks to educate pupils as persons with integrity and noble values, as well as high moral standards based on universal values and moral principles that contribute to the unity, prosperity, and well-being of individuals, countries, and global society. In this study, students' moral character is strengthened through the process of mentoring and counseling in order to produce good student character that can have a positive impact on themselves and their environment.